의료기기 통합정보를 활용한 건강보험심사평가원과 식품의약품안전처의 정보 연계 방안 - 임수연; Sooyeon Lim; 정현주; Hyeonju Jeong; 권병주; Byeong-ju Kwon (HIRA Research, 2024)
With the expansion of the medical device market, the efficient distribution and post-management of therapeutic materials have become increasingly important. Because of the transfer of the management system to the Ministry of Health and Welfare, inefficiencies arise from unlinked data between the Ministry of Food and Drug Safety (MFDS) and the Health Insurance Review & Assessment Service (HIRA). To solve this problem, we analyzed the phenomena that occur when linking information from the Therapeutic Materials Guide Map with information from the MFDS. Furthermore, we analyzed the roadmap for the “EDI (electronic data interchange) Standard Code Model Name Transition” and the Medical Device Supply Reporting System to propose improvement methods to enhance the reliability of data provided by the Integrated Medical Device Information System and integrate unlinked data of the MFDS and HIRA. When reporting medical device supply, errors can occur in the EDI codes because the EDI code data are registered directly by the manufacturers. The HIRA must be able to manage and verify the EDI code data entered by the manufacturers in the Integrated Medical Device Information System. The usage and linkage of UDI (unique device identifier) and EDI codes hold promise, particularly when using the Medical Device Supply Reporting System. Integrating medical device information from the MFDS and HIRA will enhance the efficiency of medical device management and contribute to the effective operation of health insurance systems. The Medical Device Supply Reporting System, which is unique to Korea, should be actively used for system improvements to strengthen the competitiveness of the domestic medical device industry and contribute to public health protection.